Workshop on the Sahel region-goodwill address: president of Islamic development bank - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Workshop on the Sahel Region. Workshop on Partnerships to address the challenges of agriculture in the Sahel.